The Moroccan species of Chyromyidae (Diptera) with descriptions of five new species of Aphaniosoma Becker - Ebejer, Martin J. (Zootaxa, 2016)
Nineteen species of Chyromyidae from Morocco are listed with data and compared to the fauna of the other North African countries bordering the Mediterranean. Five new species of Aphaniosoma, A. gatti, A. nigripes, A. nitidum, A. soror and A. zizense spp. n. are described and their relationships discussed and 11 species are recorded from Morocco for the first time.